The Role and Importance of Model Research in Monitoring and Supporting Production Systems - Dorota PALKA (Communications of International Proceedings, 2021)
The dynamic development of information and information technologies means that the functioning of production companies is associated with the need to implement many modern solutions, including those covering the processes of planning, assessment and production management. The purpose of their implementation is to provide enterprises with a competitive advantage and enable them to attract new customers. The competitive advantage is now associated with the company's success, which can be defined by parameters relating to the quality and speed of production, product prices, response to market demand and meeting increasingly demanding ecological and ethical requirements. Achieving economic success is of key importance, which is greatly influenced, among others, by the efficiency of the production process. This effectiveness depends on: broadly understood process safety, continuity, material consumption for production purposes, operation of technical devices, human work, costs incurred and machine efficiency. Therefore, in order to improve the efficiency of production processes, it is necessary to use the latest IT and information solutions as well as tools supporting individual stages of these processes. One of the methods supporting post-production processes is model research, based on various methods of modeling and computer simulations. Their task is to reproduce the studied phenomena in the best possible way, and then analyze them in a way that is as close to the real thing as possible. A number of benefits resulting from the use of this test method makes it very widely used in practice. The article focuses on discussing the role and importance of model research in the processes of monitoring and supporting production processes. Also presented is a tool which is now increasingly used in the form of the FlexSim program for modeling production processes. The use of this tool and many others significantly supports the implementation of these processes. Several examples of the use of this program to model some of the production processes are also presented. The presented method and examples of the application of model tests indicate their enormous potential and wide application possibilities in practice. The development of industrial automation and IT tools increasingly supports and will support the management of production processes.
Keywords: Model research; simulation; production process; FlexSim; process efficiency